2001
DOI: 10.2754/avb200170020127
|View full text |Cite
|
Sign up to set email alerts
|

Functional Development of the Small Intestine of Japanese Quail Hatched on Mir Orbital Station

Abstract: The effect of microgravity on functional development of the small intestine of Japanese quails incubated for 2-3 d and hatched on the orbital station MIR was examined. After 5 d of space flight duodenal and jejunal alkaline phosphatase (AP) activity of the experimental group was compared with the AP activity in quails of the same age hatched on the Earth (laboratory controls). Shortterm microgravity leading to decreased food intake resulted in significant increase of AP activity in both duodenal and jejunal en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The adaptive features, including different mechanisms from molecular pathways to cognitive and behavioral adaptations, to the space condition of the exact species are determined by the biology and phylogenetic history of the species [6]. There have also been numerous studies on fish models [7,8,9,10,11,12]; amphibians, such as clawed frogs [13] and ribbed newts [14,15,16,17,18]; and birds (Japanese quail) [19,20,21,22,23,24]. Reptiles are rare model objects for space and microgravity research [25,26,27,28,29,30,31,32,33,34] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The adaptive features, including different mechanisms from molecular pathways to cognitive and behavioral adaptations, to the space condition of the exact species are determined by the biology and phylogenetic history of the species [6]. There have also been numerous studies on fish models [7,8,9,10,11,12]; amphibians, such as clawed frogs [13] and ribbed newts [14,15,16,17,18]; and birds (Japanese quail) [19,20,21,22,23,24]. Reptiles are rare model objects for space and microgravity research [25,26,27,28,29,30,31,32,33,34] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of gravity in the space lab, and the resulting effect upon the quail feeding behaviour the intake of food was restricted. Lenhardt et al (2001) found slightly increased alkaline phosphatase activity in the microvilli of the enterocytes of the same quails suggesting an adaptation to utilize the restricted feed stuffs more efficiently. We suppose that the insufficient feed intake caused a mobilization of fat reserves in the body and accumulation of lipids in the liver.…”
Section: Discussionmentioning
confidence: 81%
“…In previous studies we observed that the chicks were not able to feed normally during the fi rst days after hatching due to short-term space microgravity. This leads to a signifi cant increase in the AP activity in the duodenal and jejunal enterocytes of Japanese quails on days 4-5 of age (Lenhardt et al 2001). These results indicate an altered functional development of its digestive tract, however, the response of the small intestine to hypodynamy in older chicks is poorly understood.…”
Section: Simulatedmentioning
confidence: 97%